P4.113 Reach and acceptability of an online hiv/sti testing service (getcheckedonline) among gay, bisexual, and other men who have sex with men living in british columbia, canada. (8th July 2017) - Dulai, Joshun; Salway, Travis; Thomson, Kimberly; Haag, Devon; Lachowsky, Nathan; Grace, Daniel; Edward, Joshua; Grennan, Troy; Trussler, Terry; Gilbert, Mark
Abstract : Introduction: Gay, bisexual, and other men who have sex with men (MSM) in British Columbia (BC) have a high incidence of HIV/STI, with many reporting barriers to accessing testing. An online HIV/STI testing service, Get Checked Online (GCO), was launched in 2014 to reduce these barriers. In this study we examined reach and acceptability of GCO within the MSM community. Methods: We surveyed MSM living in BC over 6 months in 2016. Participants were recruited at local pride events, bars, on the street, in sexual health clinics, through social media, and on gay hook-up apps and websites. Survey questions were analysed descriptively and included questions about the service itself, sexual health, technology use, and demographic characteristics. Results: Of 1272 participants completing the survey, 78% identified as gay and 16% as bisexual, 73% identified as White, 52% reported being single, and 55% reported living in the city of Vancouver. 32% were aware of GCO, 13% had visited the website and 3% had tested through the service (10% among the 411 men aware of GCO). Among GCO-aware participants, 50% intended to test through the service in the future (vs. 47% among GCO-unaware), 51% reported talking about GCO with others and 22% knew someone who has used it. 46% reported that at times they would use GCO over their usual place of testing. The most common benefits reported by participants were testing without waiting for an appointment (50%), getting results online (46%), and saving time (38%). The most common drawbacks were not speaking with a doctor or nurse (39%), not being sure how the service works (26%), and worrying about the privacy of one's online information (20%). Conclusion: Approximately 2 years after GCO's launch, a third of MSM in the region are aware of the service with 1 in 10 GCO-aware men testing through the service. Given high intention to use GCO, these findings highlight the importance of continuing promotion efforts to raise awareness of the service among MSM.